Analisis Pengeluaran Dana Desa Pada Pemerintahan Desa Haruru Kecamatan Amahai Kabupaten Maluku Tengah - Asfarina, Ruhu; Asrida, SE., M.Si, Wa; Pelamonia, Julie Theresya (Politeknik Negeri Ambon, 2024)
This research aims to analyze the budget realization report for the Haruru Village Government in order to increase expenditure realization in the following year. This research is quantitative research. The data used in the analysis is the 2020-2023 Expenditure Budget Realization Report. The analysis technique used is documentation and is analyzed using expenditure variance analysis, expenditure harmony and expenditure efficiency. The results of the research show that expenditure in the Haruru Village Government, seen from the expenditure variance, is generally said to be good because this analysis is categorized as a favorable variance, meaning that the realization is smaller than the budget. Because only a small portion of the funds are allocated for capital expenditures and another portion is allocated for operational expenditures, the analysis of expenditure compatibility is considered unbalanced. In addition, overall expenditure efficiency checks have been carried out well and are considered effective.